Cultivando alimentos e significados: um estudo de caso da reconexão entre produtores e consumidores no PAA - Capistrano, Milena de Oliveira Werneck de (2014)
The thesis addresses the reconnection between producers and consumers of agroecological food by means of the Food Acquisition Program for Family Farming (PAA) in Paraná. The operational dynamic of the Food Bank of Urban Rural Formation Center Irmã Araújo (CEFURIA) was investigated. This center assists the population affected by food and nutrition insecurity and social vulnerability in Curitiba and its metropolitan area. In this respect, agroecological farming families settled in the municipality of Lapa-PR implement a project mode of Simultaneous Donation of PAA. This project aims to analyze reconnect producers and consumers in the institutionalization process of this policy as a short circle commercialization of agroecological products, as well as to measure the public intervention in meeting the basic needs of individuals. It is assumed that the construction of social relationships is linked to the inherent characteristics of social agents that operate as individuals assisted by the program, and that are able to influence and 'create' reconnection factors. Furthermore, it is assumed that such social relationships are affected by normative and regulative operational dynamics that are created at a local scope by social agents that implement the Program. Finally, it is presumed that social relationships created by social agents can influence the creation and modification of shared meanings and values, as well as the behaviors and attitudes in promoting the feeling of reconnection between producers and consumers of agroecological food. This debate aims to incite a cognitive approach focusing on individual and organizational social action in the institutionalization process of a public policy that has been analyzed in recent studies due to its capability to reconfigure production, distribution and food consumption models, facing disconnections of the current food system. Thus, a qualitative methodology was applied. Participative observations and semi-structured interviews with agents located in different points of the Food Bank of CEFURIA, from production to consumption were conducted. The results were as expected. The trajectories and views of individuals and organizations involved in the Program implementation in Curitiba and in the settlement of Lapa, as well as the organizational configuration and dynamic operational created by them to execute the Program through the Food Bank of CEFURIA may influence social relationships and creation, modification and sharing of institutional elements along the food circle. These relations may influence attitudes and behaviors of the agents in order to promote reconnection between producers and consumers of food.